Does morality predict aggressive driving? A conceptual analysis and exploratory empirical investigation. (October 2020) - van den Berg, Tom G.C.; Kroesen, Maarten; Chorus, Caspar G.
Highlights: We extend Schwartz's integrated model of ethical decision making and apply it to the context of aggressive driving. The conceptual analysis shows that the moral value-aggressive driving relationship is rather indeterminate. Results show few and rather weak empirical relationships between moral values and committed aggressive driving behaviors. Abstract: Risky and aggressive driving is an important cause of traffic casualties and as such a major health and cost problem to society. Given the consequences for others, risky and aggressive driving has a clear moral component. Surprisingly, however, there has been little research on the relation between morality and risky and aggressive driving behavior. In this study we aim at addressing this gap. First, we present a conceptual analysis of the relationship between moral values and aggressive driving behavior. For this purpose, we extend Schwartz's integrated model of ethical decision making and apply it to the context of aggressive driving. This conceptual analysis shows that moral decision-making processes consist of several stages, like moral awareness, moral judgment and moral intent, each of which are influenced by individual and situational factors and all of which need to materialize before someone's generally endorsed moral value affects concrete behavior. This suggests that the moral value-aggressive driving relationship is rather indeterminate. This conceptual picture is confirmed by our empirical investigation, which tests to what extent respondents' moral values, measured through the Moral Foundation Questionnaire, are predictive of respondents' aggressive driving behavior, as measured through an aggressive driving behavior scale. Our results show few and rather weak empirical relationships between moral values and committed aggressive driving behaviors, as was expected in light of our conceptual analysis. We derive several policy implications from these results.